La Constitution Algerienne de 1989: Une passerelle entre le socialisme et l’islamisme? - Beke, Dirk (Afrika Focus, 1991)
The riots of October 1988, the most violent uprising since independence against FLN-rule, forced president Chadli Bendjedid to accelerate and to extend the constitutional reforms announced earlier. An adaption of the constitutional law to the ongoing economic liberalization-process had become a necessity, but the popular pressure now not only asked economic changes, but also profound political reform. The new constitutional text was rapidly elaborated by a small circle of persons around the President and then submitted directly to a popular referendum. In contradiction with the procedure fixed by the previous constitution, the National Assembly was not involved nor even consulted. The constitution of 1989 generates an entirely new political regime. The word "socialism", basis of the official doctrine since independence and largely confirmed by the provisions of the constitution of 1976, is banned completely. The new constitution also provides for the political responsibility of the Head of the Government and the members of the Government to the National People's Assembly, and not any more to the President only. In the chapter on fundamental freedoms and the rights of man, it is explicitly provided that the State guarantees the right to form political associations. This new timorous formulation entails the end of the one-party system and the FLN's exclusive hold on power. Some basic principles remain: Algeria is still considered a popular democratic state. Islam is the state religion and the official language is Arabic. No reference is made to the Berber language or culture. New is that the exercise of the guaranteed fundamental freedoms and rights can not be submitted any more to the imperatives of a socialist revolution. It is also stated that judges only obey to the law, they are not submitted any more to the revolutionary legality. A Constitutional Council is created to ensure that the constitution is respected but citizens have no right to submit a case, only the President and the President of the Assembly have. The tasks of the army are limited to safeguard the national independence and sovereignty; the army has no duties any more to safeguard the socialist revolution. The introduction of a responsible Government affects the presidential powers only in a minor way. The President presides over the Council of ministers, where bills are discussed. The President can ask the Assembly for a second reading of a law and this new vote requires a two-thirds majority. Only the President has the initiative for a constitutional revision. The President chairs a number of other councils. Finally the declaration of the state of emergency is depending only on the decision of the President; this attributes him large exceptional powers. Thus, the constitution of 1989 confirms a strong presidential regime but on the other hand it has introduced a real multi-party system in Algeria. More than 20 political parties are recognised. During the local elections of1990 the ruling FLN was defeated in most places by a massive victory of the islamic fundamentalist party, the FIS. A new electorial law, voted by the - still exclusive FLN - National Assembly beginning 1991, had to ensure a better result for the FLN during the forthcoming first free national elections. In June 1991 violent and even armed protest, organised by the fundamentalists against the law forced president Bendjedid to postpone elections, to declare the state of emergency but also to promise early presidential elections. Meanwhile many fundamentalists, and between them the main party-leaders, were arrested. The army played a crucial role in re- establishing public order and as a consequence gained more importance, but there were no signs that it exceeded its authority. Under present difficulties one wonders whether the constitution of 1989 will help to create a representative democratic multi-partyism, with an equitable liberal economy, whether it will help to open the way for a regime dominated by islamic fundamentalists? KEY WORDS: Algeria, constitution, internal politics